Display of fresh semen quality, frozen semen production, and field fertility of Bali bulls (Bos sondaicus) in different season - Fatmila, Dian Tria; Yudi; Purwantara, Bambang; Hasan, Fuad; Sutanto, Wahyudi Himawan (Talenta Publisher, 2025)
Bali cattle is one of Indonesia's local cattle that has high economic potential. The quality of the semen used plays an important role as a factor in the success of artificial insemination (AI) programs. Climate change, including temperature variations, rainfall, and length of solar exposure, can affect the quality of fresh semen produced by bulls. Differences in environmental conditions can affect semen characteristics, such as spermatozoa concentration, motility, and morphology, which in turn have an impact on the field fertility rate. The aim of this study is to explore the differences in male fertility based on environmental conditions that change throughout the seasons. The research method used in this study is non-experimental, using secondary data on the quality of fresh semen and frozen semen production collected from the Regional AI Center, Bali Province. In addition, this study also used data from the big data of the National Animal Health Information System (iSIKHNAS) to calculate field fertility represented by conception rate. Climate data was obtained from the Indonesian Agency for Meteorological, Climatological and Geophysics (BMKG) Bali Province, the data collected was climate data in Tabanan Regency. The differences in the appearance of fresh semen quality, frozen semen production, and field fertility were analyzed using the Independent T-Test. In this study, there was no significant difference in fresh semen quality, frozen semen production, and field fertility (P>0.05) in all parameters, but the average reproductive performance of bali bulls was higher in the rainy season than in the dry season.